Incidence and Risk of Scleral-Fixated Akreos (AO60) Lens Opacification: A Case Series. (March 2021) - Belin, Peter J.; Kim, Jang H.; Sheikh, Ahmed; Winokur, Jules; Rhee, David; Deramo, Vincent
Purpose: Postoperative hydrophilic intraocular lens opacification can lead to decreased vision and may require intraocular lens exchange. This study aims to identify the incidence of scleral-fixated Akreos AO60's (Bausch + Lomb) lens opacification and risk factors for this phenomenon. Methods: This is a retrospective case series of all patients who underwent scleral-fixated Akreos AO60 lens at our institution between January 1, 2015 and December 31, 2019. The following data were recorded: age, sex, medical history, indication for Akreos AO60 implantation, laterality, ocular history, previous ocular surgical procedures, subsequent intraocular surgical procedures after the Akreos implantation, lens opacification, visual significance of opacification, and Akreos explantation. Intraoperative and postoperative complications were recorded. Main outcome measures were the overall incidence of Akreos lens opacification as well as the incidence of these eyes undergoing subsequent intraocular surgery. Results: A total of 262 eyes of 257 patients underwent Akreos lens implantation. Overall, 2% (5 of 262) developed lens opacification. Two patients had Descemet stripping automated endothelial keratoplasty (DSAEK) concurrently with Akreos implantation. One patient underwent subsequent Baerveldt glaucoma implantation and DSAEK. The fourth patient had vitrectomy with sulfur hexafluoride gas followed by DSAEK. This represents a 25% (4 of 16) opacification rate among all patients who underwent DSAEK ( P ≤ .01, Fisher exact test). One patient developed opacification after undergoing 2 vitrectomies for retinal detachment in the absence of DSAEK. Conclusions: Akreos lens opacification can be visually significant and may occur after a retinal or corneal procedure that involves the use of intraocular gas or air.